A comprehensive review of landfill leachate treatment technologies - Wang, Jiachen; Qiao, Zhen (Frontiers in Environmental Science, 2024)
The management of landfill leachate presents a significant environmental challenge, necessitating a comprehensive and dynamic treatment approach. This comprehensive review delves into the critical issue of landfill leachate treatment, exploring its environmental impact, treatment technologies, regulatory frameworks, and the path towards sustainable management practices. This review explores the complexities of landfill leachate, emphasizing the need for sustainable waste management practices to safeguard environmental health. Our analysis highlights the evolution of conventional and advanced treatment technologies designed to mitigate these risks, focusing on membrane technologies, advanced oxidation processes, and the promising potential of emerging techniques such as adsorption and biological nutrient removal. These technologies are evaluated for their efficiency, cost implications, and sustainability impacts, underscoring the challenges and opportunities within the current landscape of leachate treatment. The review aims to provide insights into designing efficient and effective treatment systems through a detailed analysis of conventional and advanced treatment methods. By examining a case study in Changsha City, the effectiveness of a comprehensive treatment system integrating various technologies is demonstrated. The review underscores the interconnectedness of human activities, environmental health, and waste management, emphasizing the importance of a holistic approach. It stresses the continuous improvement of leachate treatment technologies and the adoption of sustainable practices to reduce the environmental footprint of landfills. Ultimately, it calls for integrating multiple treatment processes, economic considerations, and readiness to address future challenges in landfill leachate treatment, contributing to the advancement of sustainable waste management practices.